The Association between Antiphospholipid and Coagulation in Pregnant Women with Blood Clotting - Dabah Dakil Awad; Iktefa Abdul Hameed Mohammed Saeed; Maha El. Jasim (Medical Journal of Babylon)
Background: Antiphospholipid syndrome is a systemic hematological autoimmune disease characterized by a hypercoagulable state, which is associated with vascular thrombosis and/or obstetric morbidity characterized by miscarriage, fetal death, and/or premature birth. Objective: This research study aimed to estimate anticardiolipin [ACL; immunoglobulin (Ig)G and IgM] and lupus anticoagulant (LA) in pregnant women who have blood clots or who have previously miscarried and fetal intrauterine mortality. Materials and Methods: This study included 90 women, 60 of whom were pregnant women who had blood clots or had previously miscarried, as well as 30 nonpregnant women as a control group, aged from 20 to 41 years, from October 2022 to April 2023. The patients were referred to the Department of Gynecology and Obstetrics at a Teaching Hospital, Salahuddin. LA, ACL IgM, and ACL IgG were detected in serum by the enzyme-linked immunosorbent assay. Results: This study found that pregnant women have higher ACL IgM and IgG levels than nonpregnant women. The mean concentration (mean ±standard error) for ACL IgM was 23.43 ± 1.4, whereas ACL IgG was 33.11 ± 1.28, which is in contrast with the control group of ACL IgM (2.99 ± 0.22) and ACL IgG (3.51 ± 0.29). The differences were statistically significant (P = 0.0001). A significant increase in LA in pregnant women was 37.77 ± 1.14, whereas the control group had a lower mean amount of LA was 334.42 ± 1.05. Statistically significant differences were observed (P ≤ 0.05). Conclusion: Elevated levels of ACL and LA are the main cause of spontaneous recurrent abortions in women.